Identifying and predicting trajectories of binge drinking from adolescence to young adulthood - Soloski, Kristy Lee (Kansas State University, 2014)
Early binge drinking (i.e., five or more drinks on a single occasion) is associated with a greater risk of later substance abuse or dependence, and other non-alcohol related problems in adulthood, (e.g., adult civil or criminal convictions). Identifying alcohol use trajectories has mainly been limited to within single developmental periods (i.e., adolescence or emerging adulthood) or between developmental periods up until around the legal drinking age. Using N = 1,864 adolescents from the National Longitudinal Study of Adolescent Health (Add Health) dataset, this paper sought to identify trajectories of binge drinking beginning in adolescence and into adulthood using growth mixture modeling. Family factors (e.g., parent-child communication, shared activities, connectedness, and parental control) were used to predict the various trajectories. Two class trajectories were identified, a low initial-escalating group (87%), and a high initial-deescalating group (13%). Being male and having more close friends using alcohol were predictive of a greater likelihood of being in the high initial-deescalating group. Results can inform therapeutic interventions in an effort to affect an adolescent’s trajectory of use and reduce the risk of long-term heavy alcohol use.
Keywords: Adolescence; Alcohol use; Family socialization theory; Growth mixture modeling; Trajectories; Binge drinking; Individual & Family Studies (0628)